Long‐term relationships between screening rates, breast cancer characteristics, and overdiagnosis in US counties, 1975–2009. Issue 3 (5th November 2018) - Harding, C.; Pompei, F.; Burmistrov, D.; Wilson, R.
Abstract : Effects of mammography screening in the general population are disputed. Screening rates differ greatly between US counties, providing a natural opportunity to investigate effects of screening. We compared mammography screening rates with the types and outcomes of breast cancers diagnosed in US counties. The county screening rate was defined as the proportion of women age ≥40 with ≥1 mammogram in the past 2 years (range, 34–91%). Two periods were analyzed: 1975–2009 (612, 941 breast cancer cases, 195 counties) and 1996–2009 (645, 057 cases, 211–547 counties). Multiple signs of overdiagnosis were observed: First, breast cancer incidence increased as screening became common. Second, incidence stopped increasing once screening rates stabilized. Third, the increases in incidence were limited to age groups receiving screening. Fourth, the increases were larger in counties where screening became more common. Fifth, the increases were limited to small and early‐stage breast cancers (which are consistent with overdiagnosis). Sixth, compensatory reductions in large and advanced‐stage breast cancers were much smaller than the increases. Difference‐in‐differences regression analysis suggested 31% (95% CI: 28–34%) of breast cancers diagnosed in 1996–2009 were overdiagnosed. Screening rates correlated with increased incidence for all hormone receptor statuses, HER2 statuses, and grades. Reductions in breast cancer mortality during 1975–2009 were similar in screened and unscreened age groups. Overall, we found repeated signs that breast cancer overdiagnosis is widespread in the US, but the biological nature of overdiagnosed tumors remains unclear. Mortality benefits of screening, though they may be present and substantial, could not be detected at the population level. Abstract : What's new? Mammography screening is associated with reductions in breast cancer mortality and with some amount of breast cancer overdiagnosis. The extent of overdiagnosis, however, is uncertain. Here, the authors compared mammography screening and breast cancer rates in U.S. counties from 1975‐2009, identifying multiple signs of widespread overdiagnosis, including elevations in breast cancer incidence as screening use climbed and leveling off of incidence as screening rates stabilized. Analyses suggest that overdiagnosis accounted for 31 percent of U.S. breast cancer cases between 1996 and 2009. Moreover, population‐level analyses were unable to detect mortality benefits. No biological marker to identify overdiagnosis was found, however.